Importance of miRNA in SARS-CoV2 infection - De Sanctis, Drs. Juan Bautista; García, Alexis; Garmendia, Jenny; Moreno, Dolores; Hajduch, Marian; Radzioch, Danuta (Gaceta Médica de Caracas, 2020)
At the end of 2019, a new pathogen, coronavirus SARS-CoV2, was identified. The virus has infected more than 30 million people worldwide with lethality close to 5 %. SARS-CoV2 is an RNA virus. The viral genome contains 29 891 nucleotides which encode 9 889 amino acids; 5 ́-replicase (orf1/ab) four main structural proteins [Spike (S) -Envelope (E) – Membrane (M) -Nucleocapsid (N)] and open reading frame proteins. Al final del 2019, un nuevo patógeno, el coronavirus SARS-CoV2, fue identificado. El virus ha infectado a más de 30 millones de personas en el mundo entero con una letalidad cercana al 5 %. El SARS-CoV2 es un ARN virus. El genoma viral contiene 29 891 nucleótidos que codifican para 9 889 aminoácidos; 5 ́-replicasa (orf1/ab), cuatro proteínas estructurales principales [espiga (S)-Envoltura (E)-Membrana (M)-Nucleocápside (N)] y las proteínas de la región terminal ORF.